DISCOURSE POLITICAL LAW IN INDONESIA ON A COMPLETATION OF PLATO PHILOSOPHY - Adrianus M. Nggoro (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
This paper is a literature review with a comparative approach, meaning that the philosophy of Plato to study the concept of policy and law in the state of Athens, Ancient Greece. Then the authors analyze the advantages of the concept of Plato's political philosophy as a critical review of the political reform laws in Indonesia. The results of the literature review showed that from a conceptual perspective, philosophical, ideological, political jurisdiction of law in Indonesia aimed at the welfare of a just and prosperous society, in peace and prosperity, both physically and mentally, it is listed in Pancasila and the 1945 Constitution (UUD 1945). Political concept of Indonesian law is very relefan with political philosophy pioneered by Plato. But the political implications of the law of Indonesia dominant sourced on codification. The history of law in Indonesia experienced political dynamics. It was caused by political energy which dominate the role of law, so many national degradation: corruption, human rights, the financial crisis, removing P4 (as practice guidelines Pancasila). Therefore, learn to Plato, the ancient Greek philosopher. According to Plato the role of natural philosophy, philosophy of nature is very important to establish a governance structure. Relating this, the authors offer a return policy should apply P4, based on customary law and the need to establish a new state institutions, namely State Agency Professor (LTNP). LTNP of authority is a board of experts who contributed to the state policy. LTNP as a level to state institutions RI: executive; legislative and judicial).. Keywords: Political Law, Philosophy of Plato, Indonesia